Government Intervention in Poverty Alleviation in Indonesia - Ahmad Sodiq; Rintan Eka Nurnabilla; Chumeira Nidyasarta (Journal of Islamic Economics Management and Business (JIEMB), 2026)
This study discusses government intervention in poverty alleviation in Indonesia byplacing poverty as a multidimensional phenomenon that encompasses economic,educational, health, infrastructure, and socio-cultural aspects. Using a descriptivequalitative method based on literature studies, this study examines variousgovernment policies and evaluates challenges and formulates strategies to strengthenthem. The results of the study show that government intervention has made asignificant contribution to reducing poverty rates, but its effectiveness is still hamperedby inaccurate targeting, weak inter-agency coordination, infrastructure limitations,and low community participation. In addition, Islamic values such as justice,trustworthiness, and mutual assistance reinforce the urgency of transparent andempowerment-oriented governance. The implications of this study emphasize theimportance of optimizing technology, strengthening institutional capacity, andparticipatory community empowerment models as the basis for formulating povertyalleviation policies that are more adaptive, targeted, and sustainable.